Dispositivos institucionais filantrópicos e socioeducativos de atenção à infância na assistência social - Benelli, Silvio José [UNESP]; Costa-rosa, Abílio Da [UNESP] (Programa de pós-gradução em Psicologia, Pontifícia Universidade Católica de Campinas, 2013)
This study investigated Social Care as an institution that creates mechanisms for the production of subjectivity in the care of children and adolescents. For this, we used some analytical coordinates, both conjectural and structural, models of care for mapping care in confrontation in the field of Social Care. It was concluded that there was two contradictory paradigms, in the dialectical sense, organizing social care, one being the philanthropic mode and the other the socioeducative mode. The first, which is hegemonic in the field, corresponds to a care entity still organized from philanthropic care and is guided by a minority age logic, articulated by a discourse of criminalizing the lower classes. It is informally based on the legal concept of irregular situations, which would develop preventive, repressive, correctional and moralizing care practices. The construction of a socioeducative mode implies socioeducative care that aims for an effective increase in the rights of children and adolescents, based on their status as subjects and citizens, through democratic, dialogic, participatory, multi-disciplinary and fundamentally emancipatory institutional practices.

Estudou-se a Assistência Social como instituição que faz dispositivos de produção de subjetividade na atenção à criança e ao adolescente. Para tanto, utilizaram-se algumas coordenadas analíticas conjunturais e estruturais para mapear modelos de atenção assistencial em confronto no campo da Assistência Social. Concluiu-se que haveria dois paradigmas contraditórios, no sentido dialético, organizando a Assistência Social: um seria o modo filantrópico, o outro o modo socioeducativo. Ao primeiro, que é hegemônico no campo, corresponderia uma entidade assistencial ainda organizada a partir de uma atenção filantrópica pautada em uma lógica menorista, articulada por um discurso criminalizante das classes populares, informalmente baseada na noção jurídica da situação irregular, que desenvolveria práticas assistenciais preventivas, repressivas, correcionais e moralizadoras. A construção do modo socioeducativo implica uma atenção socioeducativaque visa à promoção efetiva dos direitos das crianças e dos adolescentes, a partir da sua condição de sujeitos e de cidadãos, por meio de práticas institucionais democráticas, dialógicas, participativas, multiprofissionais e transdisciplinares, fundamentalmente emancipadoras.
Institutional philanthropic and socioeducative mechanisms of childcare in the social care
Keywords: Análise institucional; Assistência social; Políticas públicas; Psicologia social; Institutional analysis; Social care; Public policies; Social psychology